Sport Climbing Programs for Developing Life Skills of Teenagers (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Life skills are skills needed to face the demands and challenges of everyday life so that these skills should be integrated in learning and various sports and recreational activities. However, studies on programs that are deliberately structured for developing life skills, especially through wall climbing activities, are scarce. This study aimed to examine the effectiveness of the intentionally structured program for life skills integrated in wall climbing activities. This research is experimental research with pretest-posttest control group design with more than one experimental group. This study involved 39 junior high school students aged 13-15 years divided into three groups randomly. The first group applied wall climbing activities based on the intentionally structured program for life skills. The second group applied wall climbing activities, while the third group was the control group. The treatment was conducted in 8 meetins, twice meetings per week, with a duration of 90 minutes for each meeting. The instrument used in this study was the Life Skill Scale for Sport (LSSS) questionnaire to measure life skills adapted from Cronin research. The results showed that the group implementing wall climbing activities integrating the intentionally structured program for life skills had a more effective impact than the group applying wall climbing activities without integrating the intentionally structured program for life skills and the control group. This study concludes that the implementation of the intentionally structured program for life skills in sport climbing activities have a significant impact on the life skill development of students.